2013
DOI: 10.2527/jas.2012-5998
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucine requirement of pigs weighing 8 to 18 kg fed blood cell–free diets1

Abstract: The aim of the present study was to determine the minimum requirement of Ile in young pigs, enabling feeding of balanced low-CP diets. Most previous studies have used experimental diets that included blood cells, which are particularly high in Leu and known to antagonize the use of Ile. One week after weaning at d 28, 100 crossbred female pigs weighing 7.9 ± 0.7 kg were allocated to 1 of 5 dietary treatments. Diets were formulated to contain 1.15 g standardized ileal digestible (SID) Lys/MJ NE and were free of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Thus, the results of the current study are in agreement with the recent studies on SID Ile:Lys requirements using blood free diets and suggesting a range between 0.50 and 0.54 SID Ile:Lys for the optimum animal performance (Wiltafsky et al, 2009;Gloaguen et al, 2013;Nørgaard et al, 2013). It should be noticed that the upper 95% confidence limits in the current study were up to 0.61 SID Ile:Lys.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Thus, the results of the current study are in agreement with the recent studies on SID Ile:Lys requirements using blood free diets and suggesting a range between 0.50 and 0.54 SID Ile:Lys for the optimum animal performance (Wiltafsky et al, 2009;Gloaguen et al, 2013;Nørgaard et al, 2013). It should be noticed that the upper 95% confidence limits in the current study were up to 0.61 SID Ile:Lys.…”
Section: Discussionsupporting
confidence: 95%
“…The impaired animal performance at high Ile intake, which is also reported by Nørgaard et al (2013) and Wiltafsky et al (2009), could be derived from the interaction among BCAA. As it has been shown previously (Wiltafsky et al, 2010), excess Leu causes more degradation of Ile.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In comparison to Leu, Val and Ile are reported to have less or no effect on the regulation of the BCKDH complex activity (Cynober and Harris, 2006;Wiltafsky et al, 2009). The results of recently published works from our group showed that Ile may also have a regulatory effect on BCAA catabolism, as an Ile excess decreases performance and plasma Leu concentration (Soumeh et al, 2014, Nørgaard et al, 2013.…”
Section: Discussionmentioning
confidence: 90%